2002
DOI: 10.1029/2000jd000247
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of Saharan dust transported over northwestern tropical Atlantic Ocean in relation to source regions

Abstract: [1] On the basis of daily Saharan dust samples collected at Sal Island (Cape Verde Archipelagos) and Barbados (Caribbean Sea) over 3 years, this study focuses on the mineralogical signature of the African sources providing dust over the tropical North Atlantic Ocean. First, the sources of the collected dust were localized by using relative clays abundance (illite-to-kaolinite ratio) combined with Meteosat infrared imagery, horizontal visibility, and backward trajectories of dusty air masses. Then, each identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
184
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(214 citation statements)
references
References 51 publications
25
184
3
2
Order By: Relevance
“…The quantification, performed via calibration with reference standard minerals, reveals that clays account for between 80% and 90% of the dust composition, regardless of the dust origin. This estimate is in good agreement with previous results of Caquineau et al (2002) for dust aerosols originating in the Sahelian belt. Our results also corroborate indirect evidence from ground-based remote sensing of the hyperspectral infrared downwelling radiance provided by Turner (2008) and suggest that the radiative signature can be described by considering that Sahelian mineral dust is composed predominantly of clay in the form of kaolinite.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The quantification, performed via calibration with reference standard minerals, reveals that clays account for between 80% and 90% of the dust composition, regardless of the dust origin. This estimate is in good agreement with previous results of Caquineau et al (2002) for dust aerosols originating in the Sahelian belt. Our results also corroborate indirect evidence from ground-based remote sensing of the hyperspectral infrared downwelling radiance provided by Turner (2008) and suggest that the radiative signature can be described by considering that Sahelian mineral dust is composed predominantly of clay in the form of kaolinite.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, this distinction is needed because of their different spectral optical properties (Sokolik and Toon, 1999). The apportionment of the total clay content into illite and kaolinite could be performed using the illite-tokaolinite (I/K) mass ratios determined by Caquineau et al (2002) for samples of equivalent origins. These authors showed that the I/K ratios vary between 0.1 for Sahelian dust to 2 for Saharan dust.…”
Section: Calculation Of the Mineralogical Compositionmentioning
confidence: 99%
“…Low K/Ch ratio (below than 1) show that the dust is originated from an Eastern Asian source. On the other hand, Saharan and North American dusts are characterized by abundance of kaolinite compared to chlorite, leading to higher K/Ch ratios (ranging from 1 to 10) (Caquineau et al 2002). In fact, as it is shown on Table 5, all collected dust samples, were originated from the North Africa region and contained higher quantities of kaolinite than chlorite (ratios between 1.1 and 2.7), with a mean K/Ch ratio value equal to 1.8 ± 0.8.…”
Section: Mineralogical Analysismentioning
confidence: 99%
“…Relative percentages in mass for kaolinite, illite and quartz are respectively 71.6, 9.1 and 19.3, as derived from measurements performed at Banizoumbou (Caquineau, 1997). The ratio between relative abundance of illite and kaolinite is 0.1 which is typical to Sahelian regions (Caquineau et al, 2002).…”
Section: The Modtran-41 Radiative Transfer Modelmentioning
confidence: 97%
“…The IDDI has been employed to the study of various applications including dust climatology (Brooks and Legrand, 2000), sources (Léon and Legrand, 2003), transport (Petit et al, 2005), composition (Caquineau et al, 2002); to validation of dust emission modeling (Marticorena et al, 1997) and of satellite desert surface mapping (Marticorena et al, 2004). Because the AOT is the most popular measure of the aerosol amount, the IDDI index is compared to it.…”
Section: Introductionmentioning
confidence: 99%